Clinical and immunologic responses in melanoma patients vaccinated with MAGE‐A3‐genetically modified lymphocytes. Issue 11 (13th December 2012) - Russo, Vincenzo; Pilla, Lorenzo; Lunghi, Francesca; Crocchiolo, Roberto; Greco, Raffaella; Ciceri, Fabio; Maggioni, Daniela; Fontana, Raffaella; Mukenge, Sylvain; Rivoltini, Licia; Rigamonti, Gianluigi; Mercuri, Santo Raffaele; et al.
Abstract: Cancer vaccines have recently been shown to induce some clinical benefits. The relationship between clinical activity and anti‐vaccine T cell responses is somewhat controversial. Indeed, in many trials it has been documented that the induction of vaccine‐specific T cells exceeds the clinical responses observed. Here, we evaluate immunological and clinical responses in 23 MAGE‐A3 + melanoma patients treated with autologous lymphocytes genetically engineered to express the tumor antigen MAGE‐A3 and the viral gene product thymidine kinase of the herpes simplex virus (HSV‐TK). HSV‐TK was used as safety system in case of adverse events and as tracer antigen to monitor the immune competence of treated patients. The increase of anti‐TK and anti‐MAGE‐A3 T‐cells after vaccination was observed in 90 and 27% of patients, respectively. Among 19 patients with measurable disease, we observed a disease control rate of 26.3%, with one objective clinical response, and four durable, stable diseases. Three patients out of five with no evidence of disease (NED) at the time of vaccination remained NED after 73+, 70+ and 50+ months. Notably, we report that only patients experiencing MAGE‐A3‐specific immune responses showed a clinical benefit. Additionally, we report that responder and non‐responder patients activate and expand T cells against the tracer antigen TK in a similar way, suggesting that local rather than systemic immune suppression might be involved in limiting clinically relevant antitumor immune responses. Abstract : What's new? The limited clinical benefit of anticancer vaccines has raised the possibility that vaccine‐induced T‐cell responses may be associated with autoimmune phenomena rather than anticancer activity in tumor tissue. Here, to determine whether melanoma‐associated antigen‐A3 (MAGE‐A3), a vaccine candidate, produces actual clinical benefit, melanoma patients were treated with autologous, genetically engineered MAGE‐A3‐expressing lymphocytes and the viral gene product thymidine kinase (TK). A correlation was detected between long‐term survival and an increase in anti‐MAGE‐A3 cells following vaccination. Furthermore, uniform responses to TK antigen suggest that local rather than systemic immune suppression may limit clinically relevant immune responses.